Human NK Cells Develop an Exhaustion Phenotype During Polar Degranulation at the Aspergillus fumigatus Hyphal Synapse - Santiago, Virginia; Rezvani, Katayoun; Sekine, Takuya; Stebbing, Justin; Kelleher, Peter; Armstrong-James, Darius (Frontiers in Immunology, 2018)
Pulmonary aspergillosis is an opportunistic fungal infection affecting immunocompromised individuals. Increasing understanding of natural killer (NK) cell immunobiology has aroused considerable interest around the role of NK cells in pulmonary aspergillosis in the immunocompromised host. Murine studies indicate that NK cells play a critical role in pulmonary clearance of A. fumigatus. We show that the in vitro interaction between NK cells and A. fumigatus induces partial activation of NK cell immune response, characterized by low-level production of IFN-γ, TNF-α, MIP-1α, MIP-1β and RANTES, polarization of lytic granules and release of fungal DNA. We observed a contact-dependent down-regulation of activatory receptors NKG2D and NKp46 on the NK cell surface, and a failure of full granule release. Furthermore, the NK cell cytokine-mediated response to leukaemic cells was impaired in the presence of A. fumigatus. These observations suggest that A. fumigatus-mediated NK cell immunoparesis may represent an important mechanism of immune evasion during pulmonary aspergillosis.